2020
DOI: 10.1017/s0029665120006916
|View full text |Cite
|
Sign up to set email alerts
|

SCFA: mechanisms and functional importance in the gut

Abstract: In recent years, the importance of the gut microbiota in human health has been revealed and many publications have highlighted its role as a key component of human physiology. Owing to the use of modern sequencing approaches, the characterisation of the microbiome in healthy individuals and in disease has demonstrated a disturbance of the microbiota, or dysbiosis, associated with pathological conditions. The microbiota establishes a symbiotic crosstalk with their host: commensal microbes benefit from the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
446
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 700 publications
(535 citation statements)
references
References 168 publications
7
446
2
5
Order By: Relevance
“…In the present study, we identi ed that the IBD group had decrease abundance in Faecalibacterium and Subdoligranulum compared to the control group, both genera have capabilities to produce butyrate. [41] However, the concentration of butyrate or other bacterial metabolite were not exanimated in the present study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In the present study, we identi ed that the IBD group had decrease abundance in Faecalibacterium and Subdoligranulum compared to the control group, both genera have capabilities to produce butyrate. [41] However, the concentration of butyrate or other bacterial metabolite were not exanimated in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…[15,38,39] As above mentioned, butyrate belongs to SCFA and is fermented from ber-rich diets by Firmucutes, [40] including family Lachnospiraceae, Ruminococcaceae and Erysipelotrichaceae. [41] Butyrate activate target cells via G-protein-coupled receptors, and participate in the maintenance of intestinal barrier, in uence the production of proin ammatory cytokines and modulate immune response. [34,42,41,40] Reduction of butyrate and butyrate-producing bacteria probably deteriorate the disrupted mucosal barrier and uncon ned in ammation in IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been reported that the levels of SCFAs, especially butyrate, are decreased in the cecum feces of rats treated with vancomycin [ 16 ], suggesting that a similar alteration might have occurred in our vancomycin-treated mice. SCFAs are important metabolites produced by the gut microbiome, and are capable of stimulating colonic epithelial cells via G protein-coupled receptors [ 19 ], thus likely affecting mucosal barrier function [ 20 , 21 ]. Thus, although we were unable to measure the level of SCFAs in the colon, mucosal barrier parameters such as permeability might be affected by alterations in the colonic luminal environment, including gut contents and their microbiome profile.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms play a critical role in maintaining epithelial barrier function in health and in regulating wound healing responses in the setting of colitis. 7 Inflammatory suppression of intestinal epithelial cell genes regulating butyrate transport, signaling, and mitochondrial oxidation is largely corrected by anti–tumor necrosis factor anti-inflammatory therapy. 8 However, complete healing only occurs in a minority of patients.…”
mentioning
confidence: 99%